2021
DOI: 10.17557/tjfc.986893
|View full text |Cite
|
Sign up to set email alerts
|

FORAGE YIELD AND QUALITY OF QUINOA (Chenopodium quinoa Willd.) GENOTYPES HARVESTED AT DIFFERENT CUTTING STAGES UNDER MEDITERRANEAN CONDITIONS

Abstract: Genotype choosing and cutting stage are very significant to obtained better forage yield and quality. However, researches about forage production from quinoa plant genotypes harvested at different cutting stages are not enough in Mediterranean conditions. This study was conducted to determine the forage yield and quality of five different quinoa genotypes (Red head, Cherry vanilla, French vanilla, Mint vanilla and Titicaca) at three different cutting stages (flowering, milky and dough). The experiment was laid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, very limited research data are available on the effect of cuttings at different growth stages of quinoa. Yilmaz et al [49] evaluated the effect of cuttings at three different stages to determine the quality and forage yield of quinoa. Their results revealed that different cutting levels had significant effects on dry forage yield and other morphological and forage quality parameters.…”
Section: Effect Of Different Treatments On Morphological and Quality ...mentioning
confidence: 99%
“…However, very limited research data are available on the effect of cuttings at different growth stages of quinoa. Yilmaz et al [49] evaluated the effect of cuttings at three different stages to determine the quality and forage yield of quinoa. Their results revealed that different cutting levels had significant effects on dry forage yield and other morphological and forage quality parameters.…”
Section: Effect Of Different Treatments On Morphological and Quality ...mentioning
confidence: 99%
“…However, it has not received adequate attention for its importance and unbelievable nutritional values, whereas public awareness of its value and potential does not yet exist (Shams, 2011;Eisa et al, 2017;Zohry, 2020;González et al, 2021). Quinoa has enormous potential; it is not only a gluten-free grain crop (Pereira et al, 2018;Villacrés et al, 2022), but it can also be used as a leafy greens crop (Abd El-Samad et al, 2018a; Pathan and Siddiqui, 2022), a fodder crop (Asher et al, 2020;Yilmaz et al, 2021) and in the food industry (Wang and Zhu 2016; Soliman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The major common ingredients are monoterpenes and phenylpropanoids, but their essential oils may vary (Padalia et al 2013). The chemical compositions of plants can be different depending on plant origin, environmental conditions (Atis et al 2012a, Yilmaz et al 2021, Ertekin, 2022, harvesting stages (Atis et al 2012b) and storage methods especially for essential oils, as well as the developmental (ontogenetic) stage (Chang et al 2009). The change in the content of secondary metabolites and their ratio within the plant may vary not only according to these factors but also according to the time of day (Gurbuz et al 2006).…”
Section: Introductionmentioning
confidence: 99%